TINJAUAN YURIDIS PERJANJIAN TAKLIK TALAK DALAM HUKUM PERKAWINAN DI INDONESIA - nurjamal, ecep (Program Studi Hukum Tata Negara, 2021)
The number of divorce cases in Indonesia is generally caused by family disharmony caused by economic problems, domestic violence, chronic illness, incompatibility and irreconcilable disputes. In addition, shigat talak is a separate problem in the divorce process where the right to divorce is in the hands of the husband, even though the wife is suing for divorce, verbality must be carried out by the husband or grant it after a judge's decision. In many cases in Indonesia, husbands do not know the mechanism of divorce by using sigat talik, so that when the wife files for divorce, the court gives a verbal decision. The method used is qualitative with a library research model, field research with a Hermeneutic-theoretical-phenomenological approach. The results of this study indicate that the divorce process using shigat talik as the executor is the autonomous right of every Islamic community to regulate it in a Shura bainahum (discuss between you, then the provisions of Article 41 letter C of Law number 1 of 1974 are included in the autonomy rights of the Islamic community and constitute the beginning of the implementation of the right to autonomy